2019
DOI: 10.3332/ecancer.2019.914
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotions in cancer patients’ decision-making

Abstract: Introduction: Despite the attempt to make decisions based on evidence, doctors still have to consider patients' choices which often involve other factors. In particular, emotions seem to influence the way that options and the surrounding information are interpreted and used. Objective: The objective of the present review is to provide a brief overview of research on decision making and cancer with a specific focus on the role of emotions. Method: Thirty-nine studies were identified and analysed. Most of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 101 publications
(132 reference statements)
2
73
1
5
Order By: Relevance
“…Such emotions can also affect their thinking process and the choices related to their cancer treatment. 18 In our study, anxiety scores decreased over time in both groups with no statistically significant difference between them. This finding supports previous studies that reported no increase in patient anxiety levels with the use of DAs.…”
contrasting
confidence: 41%
“…Such emotions can also affect their thinking process and the choices related to their cancer treatment. 18 In our study, anxiety scores decreased over time in both groups with no statistically significant difference between them. This finding supports previous studies that reported no increase in patient anxiety levels with the use of DAs.…”
contrasting
confidence: 41%
“…Both observations are congruent with the existing literature regarding the challenges individuals living with cancer face in obtaining useful information [ 1 - 4 , 9 , 11 , 12 , 14 , 15 , 38 , 39 , 42 , 50 ] and the significant role emotions play during the cancer experience [ 58 , 59 ]. The role of emotions in decision making has been well documented, with both theory and empirical data supporting that emotions affect decision making in different ways [ 60 , 61 ]. For instance, fear is associated with the interpretation of greater risk, whereas anger is associated with less perceived risk [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of emotions in decision making has been well documented, with both theory and empirical data supporting that emotions affect decision making in different ways [ 60 , 61 ]. For instance, fear is associated with the interpretation of greater risk, whereas anger is associated with less perceived risk [ 60 , 61 ]. In addition, research supports that individuals revert to less emotional states as time passes from the inciting stressor, resulting in decision making that is less reactive, and instead guided by reasoning that is more rational, better reflecting the individual’s personal values [ 60 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The last two factors extracted in the Italian adaptation of HOS scale identify people whose health perception is modulated by mood factors, such as worry and anxiety (Health Anxiety) and have negative expectation for their future health status (Health Expectation). These health orientation profiles are particularly important considering the current tendency in health psychology, which underlines the role of emotions in the modulation of health behaviours and health status [97]. For example, the Broaden-and-Build Theory by Barbara Friedrickson [98] argued that positive emotions facilitate thinking, action and decision-making.…”
Section: Discussionmentioning
confidence: 99%